(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
The humanizAS teaching innovation project at the University of Valladolid addresses the need to humanize healthcare, a priority skill in the face of the excessive technification and bureaucratization of healthcare contexts. It is implemented in five healthcare degrees in an early and multidisciplinary manner. Its core methodology is the "Interview with a Healthcare Professional," which promotes early care contact and the active role of students. After five years and 191 interviews, its evaluation by students and professionals demonstrates high success. The model, which is supported by an extensive network of collaborators, is proposed as a standard for future healthcare training.